PENGARUH PEMBERIAN AROMATHERAPI LAVENDER TERHADAP MUAL MUNTAH IBU HAMIL TM I - Deviserlina Babys (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Emesis gravidarum affects 70-80% of first-trimester pregnant women with predominant moderate nausea prevalence, requiring safe non-pharmacological therapeutic alternatives. Objective: To analyze the effect of lavender aromatherapy administration on nausea and vomiting intensity among first-trimester pregnant women at Penfui Health Center, Kupang City in 2024. Methods: Pre-experimental design with non-equivalent control group approach involving 17 respondents using total sampling technique. Lavender aromatherapy was administered three times daily for four days through inhalation of three drops of essential oil for 5-10 minutes per session. Data analysis employed Wilcoxon rank test with significance level α=0.05. Results: Before intervention, 64.70% respondents experienced moderate nausea and 35.30% mild nausea. Following lavender aromatherapy administration, significant changes occurred with 94.10% respondents experiencing mild nausea and only 5.90% moderate category. Statistical test demonstrated p-value 0.000 (α=0.05), confirming significant effect of lavender aromatherapy. Conclusion: Lavender aromatherapy effectively reduces emesis gravidarum intensity through linalool and linalyl acetate mechanisms stimulating limbic system and suppressing vomiting center. Recommendation: Lavender aromatherapy is recommended as standard complementary therapy in primary healthcare with healthcare provider training and further research using randomized controlled trials for long-term effectiveness confirmation.